TINJAUAN PERBANDINGAN PENYELENGGARAAN TELEMEDICINE ANTARA INDONESIA DAN AMERIKA SERIKAT - Wahyu Andrianto; Atika Rizka Fajrina (Masyarakat Hukum Kesehatan Indonesia, 2022)
Nowadays, the use of telemedicine is growing due to the existence of the Covid-19 pandemic, Indonesia is no exception. Even so, the United States had implemented telemedicine long before the Covid-19 pandemic struck. The United States as a superpower country is far more advanced in implementing telemedicine, in terms of technology and regulations. Therefore, this study aims to determine the implementation of telemedicine in the United States so that a new concept can be obtained that can be applied in Indonesia, considering that telemedicine has a major role in modern health services. The form of research used in this study is a normative juridical form and is a descriptive type of research. The most striking difference from the comparison results is the existence of guidelines prepared by the ATA in each health sector. Meanwhile, in Indonesia regulations regarding telemedicine is considered new. However, the existence of guidelines per health sector is important to improve the quality of health service delivery, make it easier for doctors to provide health services, create more trust, standardize the implementation, and also as a form of fulfilling the right to health according to the Constitution.